Effect of intensity of short-wavelength light on electroencephalogram and subjective alertness. (May 2020) - Lin, J; Westland, S; Cheung, V
Short-wavelength light is known to have an effect on human alertness in the night-time. However, there are very few studies that focus on the effect of intensity of light on alertness. This study evaluates the acute alerting ability of short-wavelength light of three different intensities (40 lux, 80 lux and 160 lux). Eight subjects participated in a 60-minute exposure protocol for four evenings, during which electroencephalogram (EEG) as well as subjective sleepiness data were collected. EEG power in the beta range was significantly higher after subjects were exposed to 160 lux light than after they were exposed to 40 lux, 80 lux light or remained in darkness. Also, the alpha theta power was significantly lower under 160 lux light then in darkness. These results show that the effect of intensity on alertness is not linear and further work should be done to investigate the threshold intensity that is required to produce an alerting effect.